USE OF TRADITIONAL AND COMPLEMENTARY MEDICINE TECHNIQUES IN REHABILITATION NURSING - Ricardo Picão Caldeira Rodeia; Luís Miguel Martins Faria; Pedro Miguel Alves Da Silva; Isabel De Jesus Oliveira (Associação Portuguesa dos Enfermeiros de Reabilitação, 2020)
Objective: To identify the techniques of Traditional and Complementary Medicine that rehabilitation nurses use and the perceived gains. Methodology: Study of mixed methods exploratory and descriptive study, with data collection through an online questionnaire from August to December 2019. Data were analysed using SPSS, version 23 and content analysis. Results: 31 rehabilitation nurses participated, 58.06% were women, with an average age of 42.9 ± 8.8 years and 8.6 ± 6.8 years as a rehabilitation nurse. The most representative areas of training are traditional Chinese medicine and therapeutic massage and 38.89% of the techniques used being within the area of Traditional Chinese Medicine. Participants identify more gains in the motor, sensory and respiratory areas. Conclusion: Participants use the techniques of traditional Chinese medicine to a greater extent and perceive gains from its use. It is important to quantify the gains from the integration of these techniques in rehabilitation nursing.